Protecting Batik Customers and the Existence of Pekalongan Original Batik by Augmented Reality Technology Based on Cloud Computingin Batik Label - Paminto Agung Christianto; Eko Budi Susanto; Ichwan Kurniawan (International Journal of Islamic Business and Economics (IJIBEC), 2017)
The wrong assumption stating batik printed textilebatik issimilar withoriginal batik bears a loss for batik producers, because customers tend to buy printed textilewhich are cheaper than originalones (â€œtulisâ€, â€œcapâ€ or â€œcombinationâ€ batik). The misperception used by some batik enterpreneurs who mentioned that products he sold arekinds of original batik, although theyare printed textile. It disrupts the existence of Pekalongan traditional batikas well andmany customers experience losses. This research is an effort to support Indonesian government in maintaining batik as an Indonesian cultural heritage, and Pekalongan city government in maintaining the existence of "World's city of Batik" byissuing Regional Regulation No. 6 of 2014 Pekalongan about the use of Pekalongan batik label. Through the use of augmented reality technologybased on cloud computing, it will create a "Batik Pekalongan" label which provides information about the authenticity of Pekalongan batik products through smartphones access, and convenience for Pekalongan city government or Pekalongan ASEPHI in supervising the use of the label. Therefore, it will not be misused by unscrupulous batik entrpreneurs.